2017
DOI: 10.4102/ajod.v6i0.206
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing reading abilities of learners with intellectual impairments through computer technology

Abstract: BackgroundDevelopments in the teaching of children with disabilities support pedagogy that emphasises learners’ strengths as opposed to their assumed deficiencies. Educators and mediators who advocate this view continually strive for tools and methodologies that enhance learner participation in academic environments. Computer technology is one of the tools recognised for its potential to enrich learning experiences of learners with an intellectual impairment.ObjectivesWe sought to assess the influence of text-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 42 publications
0
7
0
1
Order By: Relevance
“…This is often attributed to the problem behaviours these children present and the extra instructional skills required to teach them (Gyimah et al 2009). In a recent study that sought to assess the impact of computer technology on the reading abilities of students with intellectual disabilities in South Africa, Mosito, Warnick and Esambe (2017) found that computer-assisted learning has the potential to advance the academic achievements of students with intellectual disabilities. Our study suggests that inclusive school environments are not accommodating macrosystems for the children with IDD.…”
Section: Discussionmentioning
confidence: 99%
“…This is often attributed to the problem behaviours these children present and the extra instructional skills required to teach them (Gyimah et al 2009). In a recent study that sought to assess the impact of computer technology on the reading abilities of students with intellectual disabilities in South Africa, Mosito, Warnick and Esambe (2017) found that computer-assisted learning has the potential to advance the academic achievements of students with intellectual disabilities. Our study suggests that inclusive school environments are not accommodating macrosystems for the children with IDD.…”
Section: Discussionmentioning
confidence: 99%
“…ICT is fast becoming a key instrument in addressing reading difficulties such as poor phonics skills, poor comprehension, limited vocabulary, poor spelling and slow processing of words. This statement is supported by the study conducted by Mosito, Warnick and Esambe (2017: 3), which uncovered that reading-to-speech technology, supportive e-text and electronic books can enhance the reading abilities of learners with intellectual impairments through computer technology. Even though the focus of this case study is not on learners with intellectual impairments, it is worth acknowledging the effectiveness of ICTs as a support strategy to a variety of learning barriers such as intellectual impairment.…”
Section: Icts As a Support Strategy For Learners Experiencing Readingmentioning
confidence: 80%
“…In cases of communication breakdown with the officials manning the borders from various departments, PWDs can contact their next of kin back home and get assistance over their mobile phones and various computer-based communication platforms. Computer technology has recognised potential to enhance PWDs’ ability to participate alongside wireless technology advances (Bornman et al 2016 ; Mosito, Warnick & Esambe 2017 ). However, the absence of sound interconnectivity eliminates all this associated security and convenience reflexively creating hidden disablers for PWDs.…”
Section: Theory and Literature Findingsmentioning
confidence: 99%